Natural bio-based products for wood coating and protection against degradation: A Review - Carmen-Alice Teacă; Dan Roşu; Fănică Mustaţă; Teodora Rusu; Liliana Roşu; Irina Roşca; Cristian-Dragoş Varganici (BioResources)
Preservation of wood structures against degradation represents an old, and however, a new challenge. Wood, as a natural hybrid composite material, represents a versatile and widely exploited renewable resource for indoor and outdoor applications. Its constitutive biopolymers are subjected to intense and progressive oxidative degradation processes under environmental conditions of exposure, affecting wood’s native durability and generating significant structural and color changes, along with progressive diminution of its resistance against biological agents. One effective way to prevent wood degradation is to apply coating protective layers by chemical modification of the surface. In this context, increasing interest for improving wood coatings behavior under exposure to outdoor applications, when these are able to prevent or limit to a large extent the deleterious effects of environmental factors upon their performance, justifies enhanced research efforts to provide new effective solutions for sustainable wood protection. Recent trends in this area include use of bio-based natural products – extractives, oils, waxes, resins, biopolymers, biological control agents – for which the main classification criterion is represented by the type of protection provided, considering the large available variety of such formulations. The present paper focuses on the most recent literature data with significant assessment of specific topics related to these issues.